Oliver twist - Gudgeon, Sarah; Celija, Maja Dickens, Charles (ELI Maqbool books, 2010)
Oliver Twist is a novel by Charles Dickens, first published in 1837. It follows the life of Oliver, an orphan born in a workhouse, who faces a harsh and cruel upbringing. After escaping mistreatment, he finds himself in the dangerous underworld of London, where he is taken in by a gang of thieves led by the sinister Fagin. Through Oliver's struggles, Dickens exposes the harsh realities of poverty, crime, and social injustice in 19th-century England. Ultimately, Oliver's innocence and kindness prevail, leading him to a better life with people who care for him.